2006 International Conference on Nanoscience and Nanotechnology 2006
DOI: 10.1109/iconn.2006.340603
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of chlorpromazine binding to lipid bilayer membranes

Abstract: Abstract-With the aid of Atomic Force Microscopy (AFM) and Surface Plasmon Resonance (SPR), the interaction of chlorpromazine (CPZ) with phosphatidylcholine bilayer membranes was investigated. The interaction of CPZ had inherent effects on the transition temperature (T M ), and hence, fluidity of DMPC phospholipid membranes. It was discovered that CPZ intercalates within the membrane bilayers to form a drug/phospholipid complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[46] Other studies have revealed that CPZ-HCl at a concentration of 10 -4 M, increases the mean cellular volume of erythrocytes and the membrane area was found to expand by 2.7%. At higher concentrations, the membrane area was found to expand by 5% [50]. Lw was also observed to increase linearly as a function of temperature in the presence of CPZ-HCl both below and above the CMC ( fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…[46] Other studies have revealed that CPZ-HCl at a concentration of 10 -4 M, increases the mean cellular volume of erythrocytes and the membrane area was found to expand by 2.7%. At higher concentrations, the membrane area was found to expand by 5% [50]. Lw was also observed to increase linearly as a function of temperature in the presence of CPZ-HCl both below and above the CMC ( fig.…”
Section: Resultsmentioning
confidence: 88%
“…and hence, fluidity of DMPC phospholipid membranes. It was shown that CPZ intercalates within the membrane bilayers to form a drug/phospholipid complex [50].…”
Section: Resultsmentioning
confidence: 99%